2012
DOI: 10.2337/dc12-0271
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of Insulin Glargine After Repeated Daily Subcutaneous Injections in Subjects With Type 2 Diabetes

Abstract: OBJECTIVETo investigate concentration of plasma insulin glargine after its subcutaneous dosing compared with concentration of its metabolites 1 (M1) and 2 (M2) in subjects with type 2 diabetes.RESEARCH DESIGN AND METHODSNine subjects underwent a 32-h euglycemic glucose clamp study (0.4 units/kg glargine after 1 week of daily glargine administration). Glargine, M1, and M2 were measured by a specific liquid chromatography-tandem mass spectrometry assay.RESULTSGlargine was detected in only five of the nine subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
52
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 10 publications
7
52
0
Order By: Relevance
“…The results are consistent with previous observations at lower glargine doses (#0.8 units/kg) in which sampling at 12 h could still, in some cases, detect glargine (M0) in plasma (1,2). A previous study in T2D on high glargine doses failed to detect M0, but samples were determined only .6 years after storage of blood samples drawn and processed under unspecified conditions, likely not suitable to preserve M0 (5).…”
supporting
confidence: 81%
See 3 more Smart Citations
“…The results are consistent with previous observations at lower glargine doses (#0.8 units/kg) in which sampling at 12 h could still, in some cases, detect glargine (M0) in plasma (1,2). A previous study in T2D on high glargine doses failed to detect M0, but samples were determined only .6 years after storage of blood samples drawn and processed under unspecified conditions, likely not suitable to preserve M0 (5).…”
supporting
confidence: 81%
“…Epidemiological studies indicate that the risk of cancer is especially elevated in obese individuals with insulin-resistant diabetes requiring high insulin doses (4). Unmodified insulin glargine has been suggested to confer a higher risk of cancer (3), but prior studies have shown that, at usual doses, an active metabolite (M1) with actions similar to human insulin is the main circulating molecule after glargine injection (1,2).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…2). Lucidi et al (11) have reported that after injection, insulin glargine is rapidly and almost completely metabolized to M1 (21A-Gly-insulin) and that serum insulin concentrations measured by RIA closely correspond to circulating M1 concentrations. In all profiles, maximum concentrations of serum insulin were reached at 12 h (median), with serum insulin concentrations falling approximately twofold by 24 h postinjection.…”
Section: Pharmacokineticsmentioning
confidence: 99%